Numerical analysis on torsional behavior of rectangular and square CFDST members. (June 2022) - Lu, Guobing; Su, Meini; Zhou, Xuhong; Deng, Xiaowei; Bai, Yongtao; Wang, Yuhang
Abstract: This paper numerically investigated the behavior of rectangular and square concrete-filled double skin steel tubular (CFDST) members under torsion. The finite element model of rectangular and square CFDST members was established and verified against the test results for the members under cyclic torque. The comparison of the finite element analysis results and experiment results show that the comprehensive finite element model can accurately predict the torsional behavior of rectangular and square concrete-filled double skin steel tubular members. Parametric analyses by using the calibrated finite element model were conducted to investigate the influence of various parameters, such as hollow ratio, concrete strength, yield strength and cross-sectional steel consumption of steel tubes on the torsional behavior of rectangular and square CFDST members. Based on the mechanical analysis and regression analysis methods, the design formula was proposed to predict the torsional capacity of rectangular and square CFDST members. The comparison results show that the proposed formula for predicting the torsional capacity of rectangular and square CFDST members has good accuracy. Highlights: Finite element analysis was conducted to investigate the cyclic torsional behavior of rectangular and square CFDST members. The effect of sandwiched concrete on the failure mode of rectangular and square CFDST members under torque was discussed. Parametric analyses were conducted to study the influence law of key parameters on the torsional capacity of CFDST members. Mechanism of rectangular and square CFDST members under torque was analyzed. Design formulae were proposed to predict the torsional capacity of rectangular and square CFDST members.